Role of Cystatin C and glomerular filtration rate in diagnosis of kidney impairment in hepatic cirrhosis patients. Issue 20 (May 2017) - Wang, Dong; Feng, Jia-Fu; Wang, An-Qun; Yang, Yu-Wei; Liu, Yun-Shuang
Abstract : Abstract: Hepatic cirrhosis is often accompanied by functional kidney impairment, which may be reversed if early treatment is promptly administered. This study aimed to investigate the role of Cystatin C and Cystatin C estimated glomerular filtration rate in the diagnosis of kidney impairment in patients with hepatic cirrhosis. Four hundred sixty five patients with hepatic cirrhosis were recruited. Serum creatinine and Cystatin C were determined, and their estimated glomerular filtration rates were calculated. The area under the receiver-operating characteristic curve (area under curve [AUC]) of Cystatin C and Cystatin C estimated glomerular filtration rate was significantly larger than that of serum creatinine and serum creatinine estimated glomerular filtration rate, respectively ( P = .000). When the optimal cut-off value and upper reference limit were used, similar sensitivity, misdiagnosis rate, and diagnostic consistency were only observed in Cystatin C estimated glomerular filtration rate ( P > .05). Cystatin C and Cystatin C estimated glomerular filtration rate are superior to serum creatinine and serum creatinine estimated glomerular filtration rate in diagnosis of secondary kidney impairment, and Cystatin C estimated glomerular filtration rate has a better performance as compared with Cystatin C. However, it is not a measured parameter, and thus the lab should determine its own optimal cut-off value.